2020
DOI: 10.3892/etm.2020.8507
|View full text |Cite
|
Sign up to set email alerts
|

Fast‑track extubation in patients after intracranial hematoma surgery

Abstract: Early extubation, also known as fast track, is desirable after intracranial hematoma surgery to avoid ventilator-associated complications associated with admission to an intensive care unit (ICU). The objective of the present study was to determine whether ICU stay and ventilator-associated complications are reduced in patients who received surgery for intracranial hematoma if they are extubated early. A total of 17 patients were randomly assigned to two groups: In Group 1, patients were extubated early or usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Also, Cata et al demonstrated that delayed extubation of subjects that underwent craniotomies was associated with a longer hospital stay compared to those who had early extubation in the surgery room [32], [33]. Early extubation is desirable after intracranial procedures to avoid complications associated with admission to an intensive care unit (ICU) [34]. Sixty-three percent of patients in our report were extubated in the operating room or immediately after ICU admission.…”
Section: Discussionmentioning
confidence: 59%
“…Also, Cata et al demonstrated that delayed extubation of subjects that underwent craniotomies was associated with a longer hospital stay compared to those who had early extubation in the surgery room [32], [33]. Early extubation is desirable after intracranial procedures to avoid complications associated with admission to an intensive care unit (ICU) [34]. Sixty-three percent of patients in our report were extubated in the operating room or immediately after ICU admission.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, as anesthesia providers, we would aggressively administer sedatives, opioids or anti-hypertensives to provide those patients a smooth and calm emergence from anesthesia [ 3 ]. If possible, we would remove the endotracheal tube as early as possible in this patient group, which is to prevent them from developing ventilator-associated complications in the later intensive care [ 4 ]. Endotracheal extubation performed on the patients under deep anesthesia and with fully recovered muscle power (deep extubation) has been applied in eye surgeries and craniotomies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It mainly uses the perioperative optimization measures confirmed by evidence-based medicine to help patients reduce stress and prevent postoperative dysfunction [ 10 ]. However, clinical practice found that the nursing effect of using FTS alone for surgical patients was limited [ 11 , 12 ]. Studies have pointed out that FTS care for patients undergoing spinal surgery combined with other optimized care modes may have a positive impact on improving the patients' postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%